ISLAMIC COUNSELING (BEHAVIOUR THEORY) IN DEALING WITH TRUANT BEHAVIOUR - Hafsoh Fadilla, Fariza; Subhi, Muhamad Rifa'i (INSTITUT AGAMA ISLAM NEGERI METRO, 2024)
Truancy behavior in students is a problem that often occurs in schools, with many factors behind it. The urgency of this research is to discuss ideal lessons, aspects of truancy, the impact of truancy. Uniquely, this research is based on one of the theories in psychology, namely the behavior theory coined by Burrhus Federick Skinner. Behaviorism theory is also applied to group guidance and individual counseling. The research method used in this research is qualitative, field research type with data collection techniques using interviews, the analysis method used is descriptive analytical. The results after interviews with BK teachers at SMP Darul Hikam skipping class have various causes both internal and external. Prevention of skipping class by creating a pleasant learning atmosphere such as interspersed with games. After several times of group guidance and individual counseling by applying behavior theory to children who skipped class, the child began to leave his habit of skipping class. According to the counseling teacher, the counseling above will be more effective coupled with other theories such as humanistic, CBT and REBT.